Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.3389/fmicb.2016.00452
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Evaluation of the Antioxidant, 3,5-Dihydroxy-4-ethyl-trans-stilbene (DETS) Isolated from Bacillus cereus as a Potent Candidate against Malignant Melanoma

Abstract: 3,5-dihydroxy Q1 -4-ethyl-trans-stilbene (DETS) is a natural stilbene, which was first identified as bioactive bacterial secondary metabolite isolated from Bacillus cereus associated with a rhabditid entomopathogenic nematode. The present study was intended to investigate the antioxidant and anticancer activity of this compound in vitro. Antioxidant activity was investigated by assaying DPPH free radical scavenging, superoxide radical-(O2..) scavenging, hydroxyl radical scavenging and metal chelating activity,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 61 publications
0
3
0
Order By: Relevance
“…This is in accordance with Csepregi et al, who pointed out that strong antioxidant activity, particularly determined by FRAP assay, is positively associated with the presence of catechol structure in ring-B and 3-hydroxyl group in ring-C of catechins and flavonols [ 59 ]. The strongest correlation between values of FIC assay and anticancer activity against malignant melanoma cancer cell line—also results of the previous study—indicates that chelating agents may play an important role in reducing the concentration of the catalyzing transition metals in ROS-mediated melanoma carcinogenesis [ 60 ]. The anticancer effect on lingonberry fractions was not related to the doubling time of cell lines.…”
Section: Discussionmentioning
confidence: 53%
“…This is in accordance with Csepregi et al, who pointed out that strong antioxidant activity, particularly determined by FRAP assay, is positively associated with the presence of catechol structure in ring-B and 3-hydroxyl group in ring-C of catechins and flavonols [ 59 ]. The strongest correlation between values of FIC assay and anticancer activity against malignant melanoma cancer cell line—also results of the previous study—indicates that chelating agents may play an important role in reducing the concentration of the catalyzing transition metals in ROS-mediated melanoma carcinogenesis [ 60 ]. The anticancer effect on lingonberry fractions was not related to the doubling time of cell lines.…”
Section: Discussionmentioning
confidence: 53%
“…Preclinical studies have demonstrated that antioxidant supplementation leads to selective melanoma cell death through increased ROS-scavenging activity mediated by elevated SOD and catalase activity [35-37]. By contrast, dietary polyphenol antioxidants such as like resveratrol, tocopherol, and quercetin exert direct ROS-scavenging activity and have produced highly variable preclinical and clinical outcomes [38].…”
Section: Role Of Ros In Melanomamentioning
confidence: 99%
“…It down-regulates the expression status of major molecules contributing to melanoma progression and arrests the cells at S-G2 transition state of the cell cycle. (Nath et al, 2016). In another study, the antibiotic 3,5-dihydroxy-4-ethyl-trans-stilbene ES produced by Xenorhabdus luminescens was found to be effective against both gram-positive and some gram-negative bacteria.…”
Section: Discussionmentioning
confidence: 97%